2017
DOI: 10.1016/j.je.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL4 , IL13 , and IL4R polymorphisms with gastrointestinal cancer risk: A meta-analysis

Abstract: BackgroundPrevious studies have suggested that IL4, IL13, and IL4R are associated with serum IgE levels and allergies, and common variants of these genes may alter cancer risk. To clarify these associations, we conducted a meta-analysis to investigate the associations of IL4, IL13, and IL4R polymorphisms with gastrointestinal cancer risk.MethodsWe used 27 eligible case–control studies describing the associations of six polymorphisms of IL4, IL13, and IL4R with gastrointestinal cancer risk to calculate summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
1
11
0
1
Order By: Relevance
“…We found that IL-4 rs2070874 T>C polymorphism seemed to be a protective factor for ESCC development. Our findings were similar to a previous meta-analysis that suggested that the IL-4 rs2070874 C allele could be associated with a decreased susceptibility of gastrointestinal cancer [ 14 ]. A functional study indicated that the IL-4 rs2070874 allele C could promote a higher level of IL-4 in plasma [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that IL-4 rs2070874 T>C polymorphism seemed to be a protective factor for ESCC development. Our findings were similar to a previous meta-analysis that suggested that the IL-4 rs2070874 C allele could be associated with a decreased susceptibility of gastrointestinal cancer [ 14 ]. A functional study indicated that the IL-4 rs2070874 allele C could promote a higher level of IL-4 in plasma [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…IL4 is also involved in radiation-induced aggressive tumor behavior in human cancer cells [ 30 ]. Clinical-based studies suggest that polymorphisms of IL4 and IL4R can affect susceptibility to gastrointestinal cancer [ 31 ]. Moreover, IL4 promotes M2 macrophage activation, which further induces cancer metastasis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several previous meta-analyses also concerned about IL-4R and tumorigenesis. Cho et al 50 demonstrated a reduced risk of GC for rs1801275, but they mixed the gastric cancer, esophageal cancer, pancreatic cancer and colorectal cancer, without any subgroup analysis of cancer type. Wang et al 51 performed a meta-analysis about IL-4R and cancer risk on rs1801275, rs1805010 and rs1805015, however, they only enrolled 36 studies, and didn't adjust the P value of Q-test, which might lead to statistical error.…”
Section: Discussionmentioning
confidence: 99%